2022
DOI: 10.3389/fnut.2021.805955
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet and Its Association With Sleep Quality and Chronotype Among Youth: A Cross-Sectional Study

Abstract: BackgroundEvidence indicates that many university students have poor adherence to a healthy diet accompanied by unhealthy lifestyle behaviors. Chrono-nutrition is an emerging field of research that examines the pattern of optimum daily activity in relation to the human's dietary patterns, and their reflections of variable health indicators such as sleep quality. However, there is a scarcity of research that examines the relationship between adherence to the healthy eating pattern, like the Mediterranean diet (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 80 publications
(104 reference statements)
2
22
0
Order By: Relevance
“…Other studies have reported associations between evening chronotypes and intake of specific foods, showing highly variable results [4]. Results of recent studies also suggest that evening chronotype is associated with a lower adherence to healthy dietary patterns such as the Mediterranean diet [58,59]. In the current study, we did not analyse associations with intakes of specific food, nutrients or dietary patterns in order to keep the focus on meal timing.…”
Section: Associations With Chrononutritionmentioning
confidence: 86%
“…Other studies have reported associations between evening chronotypes and intake of specific foods, showing highly variable results [4]. Results of recent studies also suggest that evening chronotype is associated with a lower adherence to healthy dietary patterns such as the Mediterranean diet [58,59]. In the current study, we did not analyse associations with intakes of specific food, nutrients or dietary patterns in order to keep the focus on meal timing.…”
Section: Associations With Chrononutritionmentioning
confidence: 86%
“…Following the literature search and articles selection, 17 studies were included in the present review [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. A summary of the included studies and findings is reported in Table S1 .…”
Section: Main Findingsmentioning
confidence: 99%
“…Poor adherence to MedDiet has been found among the Lebanese adult University students ( 20 ) and the adult population during the COVID-19 outbreak and the economic crisis ( 21 ). Other studies assessed the adherence to MedDiet in adolescents ( 22 , 23 ) and among youth ( 24 ). However, in Syria, little is known about the adherence to MedDiet.…”
Section: Introductionmentioning
confidence: 99%